2023
DOI: 10.5468/ogs.22131
|View full text |Cite
|
Sign up to set email alerts
|

Doppler ultrasound investigation of female infertility

Abstract: This study reviewed recent advances in the use of Doppler ultrasonography for the management and prediction of female infertility outcomes of assisted reproductive technology (ART). Color or power Doppler and three-dimensional power Doppler ultrasound can be used to measure vessels near the ovaries, uterus, and endometrium to assess blood flow. Increased blood flow and reduced resistance to the ovaries, uterus, and endometrium are associated with improved pregnancy outcomes, and their measurement has been sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
0
4
0
1
Order By: Relevance
“…The backward stepwise selection in the logistic regression model also revealed that impedance to uterine artery blood flow (i.e., the PI level) was a confounder in this dataset. Studies have described the importance of uterine PI levels that were measured using Doppler ultrasound investigations in IVF–ET cycles [ 31 34 ]. One study revealed a positive correlation between IVF outcomes and the uterine scoring system for reproduction, which incorporates the PI level, endometrial thickness, endometrial layering, endometrial motion, endometrial blood flow in zone 3, and myometrial blood flow [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The backward stepwise selection in the logistic regression model also revealed that impedance to uterine artery blood flow (i.e., the PI level) was a confounder in this dataset. Studies have described the importance of uterine PI levels that were measured using Doppler ultrasound investigations in IVF–ET cycles [ 31 34 ]. One study revealed a positive correlation between IVF outcomes and the uterine scoring system for reproduction, which incorporates the PI level, endometrial thickness, endometrial layering, endometrial motion, endometrial blood flow in zone 3, and myometrial blood flow [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have described the importance of uterine PI levels that were measured using Doppler ultrasound investigations in IVF–ET cycles [ 31 34 ]. One study revealed a positive correlation between IVF outcomes and the uterine scoring system for reproduction, which incorporates the PI level, endometrial thickness, endometrial layering, endometrial motion, endometrial blood flow in zone 3, and myometrial blood flow [ 34 ]. Steer et al and Cacciatore et al asserted that PI level > 3.0 on the day of ET was associated with low uterine receptivity, and implantation became unachievable when the PI levels were > 3.3 [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the nonpregnant state, UBF serves the crucial role of facilitating endometrial growth and vascularity, as well as contributing to the readying of the endometrium for the implantation of fertilized ova. 52–54 Given that the uterine vasculature is a high resistivity vascular bed in the nonpregnant state, impedance to blood flow to the uterus is determined mostly by vascular resistance, which, in turn, is determined mainly by myogenic tone and the modulatory effects of vasodilatory factors. 9 , 55 , 56 The UA senses and responds to the cyclical stretch from systemic pressure that drives UBF, and this leads to the generation of a 2-component flow velocity Doppler waveform comprising peak systolic and end diastolic velocities, mimicking the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Васкуляризація ендометрія та матки допомагає прогнозувати результати вагітності. Тому удосконалені допплерівські ультразвукові технології можна використовувати для діагностики жіночого безпліддя маткового походження [28].…”
Section: б е з п л і д д я т а п л а н у в а н н я с і м ' їunclassified